The effect of styrene-butadiene rubber modification on the properties of asphalt binders: Aging and restoring. (17th January 2022) - Che, Tiankai; Pan, Baofeng; Li, Yudong; Ge, Dongdong; Jin, Dongzhao; You, Zhanping
Highlights: Styrene-butadiene rubbers (SBR) latex was used as an additive to rejuvenate aged asphalt binder. Rheological properties and low-temperature performance of SBR rejuvenated asphalt were evaluated through DSR and BBR tests. Aging and rejuvenation mechanisms were discussed in FM and FTIR tests. SBR latex is an effective and promising rejuvenator in the recycling of reclaimed asphalt pavement. Abstract: The aging of asphalt binders has been a critical issue affecting the reuse of reclaimed asphalt pavement (RAP). This paper aims to investigate the modification effect of styrene-butadiene rubber (SBR) latex in restoring the original performance of aged asphalt binders. The binder samples were prepared using short-term aged asphalt binders with 7% SBR latex and 10% ZGSB (a light oil-based rejuvenator), respectively. The rheological ability, low-temperature performance as well as microscopic characteristics of rejuvenated asphalt binders were evaluated through a series of testing devices, involving Dynamic Shear Rheometer (DSR), Bending Beam Rheometer (BBR), Fourier Transform Infrared (FTIR) spectrometer, as well as Fluorescence Microscopy (FM). The DSR results demonstrated that adding SBR latex increased the viscosity of aged asphalt while ZGSB decreased it, indicating that SBR improved the rutting resistance of aged asphalt at high temperatures. The BBR test revealed that SBR was as effective as ZGSB in enhancing the low-temperature cracking resistance of aged asphalt, but SBR performed better in the evaluation of anti-aging performance. The FTIR and FM tests demonstrated that the modification effect of SBR latex originated from the elasticity recovery, high stability, and good dispersion in aged asphalt binders.